STRATEGI PENGUATAN BRANDING UMKM MELALUI PEMBUATAN BANNER DAN PEMETAAN PERSEBARAN USAHA SEBAGAI UPAYA MENINGKATKAN PROMOSI POTENSI LOKAL DI DESA TAJI - Aprilia Setiani (PENDIMAS: Jurnal Pengabdian Masyarakat, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in improving the local economy. However, most MSMEs in Taji Village, Juwiring District, Klaten Regency, still face challenges in branding, promotion, and accessibility of business information. This community service activity aims to strengthen MSME branding through banner creation and the development of Google Maps-based business distribution maps. The method used is a qualitative approach with observation, interviews, documentation, and mentoring for MSMEs. The activity stages include identifying needs, designing promotional media, creating banners, and developing MSME distribution maps. The results show that banners can enhance visual identity, strengthen business image, and facilitate public recognition of products and business locations. The MSME distribution map also serves as an information medium that facilitates public access to business locations while providing supporting data for the village government in developing local economic development strategies. In addition to producing promotional media, this activity increases MSMEs' understanding of the importance of branding as an effort to increase business competitiveness. Thus, the use of banners and MSME distribution maps has been proven to support increased business visibility and the sustainable development of local economic potential.